2021
DOI: 10.1016/s2666-5247(21)00184-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immunodominant Bartonella bacilliformis proteins: a combined in-silico and serology approach

Abstract: Background Bartonella bacilliformis is the aetiological agent of Carrión's disease, a biphasic and highly lethal illness formerly restricted to the South American Andes that is now spreading to adjacent areas. Reliable serodiagnostic approaches and vaccines are urgently needed. In this study, we aimed to identify immunodominant proteins of B bacilliformis and to establish novel and reliable serodiagnostic tools. MethodsWe used a reverse vaccinology approach in combination with an analysis of heterologous genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 29 publications
4
10
0
3
Order By: Relevance
“…berkhoffii genotype III, were also not reactive to these synthetic peptides, suggesting that three-dimensional epitope conformation is likely of critical importance for the documentation of Pap31 seroreactivity. These findings are consistent with the poor seroreactivity results of B. bacilliformis Pap31 linear epitopes reported in a previous study [35], where only 2 of the 26 Peruvian patients with B. bacilliformis infection were reactive to B. bacilliformis Pap31 linear epitopes in line blots. It is also possible that B. henselae Pap31 peptide epitopes represent a minimally immunogenic region of the B. henselae Pap31 protein, and hence were not reactive with sera from B. henselae IFA-positive dogs and humans in this current study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…berkhoffii genotype III, were also not reactive to these synthetic peptides, suggesting that three-dimensional epitope conformation is likely of critical importance for the documentation of Pap31 seroreactivity. These findings are consistent with the poor seroreactivity results of B. bacilliformis Pap31 linear epitopes reported in a previous study [35], where only 2 of the 26 Peruvian patients with B. bacilliformis infection were reactive to B. bacilliformis Pap31 linear epitopes in line blots. It is also possible that B. henselae Pap31 peptide epitopes represent a minimally immunogenic region of the B. henselae Pap31 protein, and hence were not reactive with sera from B. henselae IFA-positive dogs and humans in this current study.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, while assessing B. bacilliformis recombinant Pap31 for the diagnosis of Oroya fever, the authors demonstrated that Pap31 antigens were highly induced in growing cultures of B. bacilliformis and were immunologically recognized dominant proteins in infected humans, supporting the application of Pap31 for the ELISA and WB diagnosis of human Bartonelloses [27]. Dichter et al (2021), using a reverse vaccinology approach in conjunction with an immunoproteomic approach, also highlighted the potential utility of Pap31 as an immunodominant target recognized by the serum samples obtained from Peruvian patients infected with B. bacilliformis [35]. In another study, B. bacilliformis recombinant pap31 was not reactive with sera from patients with Coxiella burnetti, Brucella spp., or B. henselae infection, supporting a lack of recombinant B. bacilliformis Pap31 cross-reactivity with these microorganisms [34].…”
Section: Discussionmentioning
confidence: 90%
“…The antigenicity of Pap-31 was confirmed by Angkasekwinai et al (2014) [48] and Gomes et al (2016) [10]. Similarly, Pap-31 was detected in the study by Dichter et al (2021) [38](see section 4.3 on Known Proteins). Furthermore, Gomes et al (2021) [11] identified immunogenic peptides within Pap-31 and SCS-α, establishing their inter-and intrageneric discrimination capacity.…”
Section: Porins B Bacilliformis Porins Have Been Analyzedsupporting
confidence: 72%
“…B. bacilliformis outer-membrane and extracellular proteins have been analyzed by the identification of epitopes in the design of an artificial multi-epitope protein with positive results in murine model [37]. In a recently published article, Dichter et al [38] tested the immunogenicity of 22 candidate B. bacilliformis proteins identified by a reverse vaccinology approach using Vaxign-1 software. The present study identified 19 exact or homologs of these proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation